Analisis Nilai-Nilai Pendidikan Karakter dalam Novel Suluh Rindu Karya Habiburrahman El-Shirazy - Windi Wildatul Mala; Hayati, Fitroh; Pratikno, Heru (UNISBA Press, 2024)
Abstract. This study aims to understand, explore, and analyze the values of character education in the novel